Logistics Software from a Logistics Management and Management Information Systems (MIS) Perspective - Gruenwald, Hermann (Information Management and Business Review, 2013)
The logistics profession has undergone severe changes over the last few decades, replacing muscle power with brain power. The virtual aspect of logistics has become equally important to the physical realm of transportation and warehousing. Supply Chain Management (SCM) deals with getting the right stuff to the right people at the right time in the right amount. To accomplish this task there are a number of more or less integrated logistics software application. Demand forecasting models based on historical data from data marts and data warehouses with built in seasonality and pricing models. Load planning software to appropriately palletize, containerize and load trucks and vessels. Route planning software with real time traffic and weather updates to reduce time and fuel costs. Electronic documents to accompany the shipment from purchase order, letter of credit to customs clearing and back-haul charges. Logistics software has many aspects and may be viewed differently from a software developer and user perspective. This study compares the perception of logistics software by management information systems (MIS) and logistics management students (Logistics) in Thailand. Some of the aspects include: user friendliness, ease of use, features and benefits, technical limitations.